Glomerulopatias secundárias à ehrlichiose monocítica canina crônica - Kikuchi, Erica Solange Caetano [UNESP] (2015)
Canine monocytic ehrlichiosis (CME), is an infectious disease of high incidence in clinical routine, caused by Ehrlichia canis, an obligate intracellular gram-negative bacterium and transmitted by the tick Rhipicephalus sanguineus. This work aimed to evaluate the histopathological lesions in kidneys and spleen caused by CME, as well as the parameters of serum biochemistry urea, creatinine, albumin and globulin. To this end, 16 dogs showed mean values of urea (90,18mg / dl) and creatinine (1,62mg / dl) were above the normal reference values for dogs; albumin showed values below normal averaging 2.01g / dl, while globulin remained within the average with 3,58g / dl. The histopathological analysis consisted of the evaluation of cortical and medullary region of the kidney and splenic parenchyma. The most prevalent morphological changes were the thickening of the basement membrane, synechia formation, tubular degeneration and necrosis. As for glomerulonephritis the one that presented the highest occurrence was the mesangial type in 62.5% (10/16) of dogs. As for the splenic changes 43.7% (7/16) of the dogs developed hypoplasia of lymphoid follicles, and 87.5% of them (14/16) had plasma accumulation in the parenchyma. The statistical analysis of correlation between the variables, showed positive correlation between the urea concentration and hyperplasia of the glomerular epithelial cells, and also a positive correlation between creatinine and hyperplasia of mesangial cells and tubular dilation; and between the concentration of globulin and infiltrate of plasma cells. Negative correlation was observed for albumin and plasma cell infiltration. In spleen, enlarged lymphoid follicles and urea had positive correlation, whereas albumin and plasma cell infiltrates showed a negative correlation. There was a predominance of mesangial glomerulonephritis, and the plasma cell infiltrate probably plays an essential role in the immunopathology of injuries